The impact of increased liquidity on profitability: Insights from Cambodian commercial banks - Siphat Lim; Edman Flores; Casey Barnett (Banks and Bank Systems, 2025)
This study examines the important but underexplored link between liquidity levels and profitability in commercial banks in Cambodia, a topic of great relevance for both bank managers and policymakers seeking to bolster financial stability. By analyzing data spanning 12 years (2011 to 2022) from 22 banks, the study applies a variety of panel data models, such as pooled ordinary least squares (OLS), fixed effects (FE), random effects (RE), and the one-step generalized method of moments (GMM). The findings reveal a statistically significant negative impact of liquidity on profitability across all static panel data models, with coefficients of –1.3005 (pooled OLS), –0.9786 (FE), and –0.9966 (RE), each statistically significant at varying levels. The dynamic panel data model (one-step GMM) further confirmed this negative relationship, showing a coefficient of –0.3588. It also highlighted a robust positive effect of lagged profitability, with a coefficient of 0.7491. Interestingly, the study found that only bank-specific factors, such as operating expenses and net interest margin, consistently influenced profitability across both static and dynamic panel models. On the other hand, macroeconomic factors like inflation were shown to negatively affect profitability, underscoring the need for sound bank management practices and well-designed regulatory policies. AcknowledgmentsWe sincerely appreciate the financial support from the management of CamEd Business School, which made it possible for us to submit this paper for publication.